ERKIN VOHIDOV’S CONTRIBUTION TO UZBEK SATIRICAL LITERATURE - Omonboyeva Gulhayo Umarjon qizi (Modern American Journals, 2026)
Satire occupies a central position in Uzbek literature as a means of social criticism and moral reflection. This article examines the contribution of Erkin Vohidov to the development of Uzbek satirical literature, with particular attention to the linguistic, stylistic, and ideological features of satire in his poetry. The research applies qualitative textual, stylistic, and discourse analysis to selected poems in order to identify dominant satirical strategies and their social functions. The findings show that Vohidov’s satire transcends humor and irony, functioning as a form of ethical discourse and civic engagement that significantly enriched modern Uzbek poetic tradition.
Keywords: Uzbek literature, satire, Erkin Vohidov, poetic discourse, social criticism